PERAN GURU PAI DALAM PENINGKATAN PRESTASI BELAJAR SISWA DI SDN ALANG-ALANG 1 CARUBAN JOGOROTO JOMBANG - Hasanah, Nur; Ya'cub, Mihmidaty; Riza, Julianne Kamilia (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
Learning achievement is an aspect of the skills possessed by students as a result of the efforts and learning activities undertaken, seen as an important indicator in the whole educational process in general. Thus, as someone who has an important role in determining the success or failure of a learning process, a teacher must be able to act as a multidimensional human being, meaning that the teacher's role in learning is not just teaching, but further, namely educating, guiding, providing convenience (facilitator). ), and motivate students to be more active and passionate in learning. A teacher must be able to deliver students to achieve educational goals as evidenced by grades and report cards. To realize the creation of student learning outcomes include cognitive, affective, and psychomotor aspects. The purpose of this study is to discuss the role of PAI teachers in increasing learning achievement at SDN Alang-Alang Caruban I Jogoroto Jombang and explained about learning achievement at SDN Alang-Alang Caruban I Jogoroto Jombang. The method in this research is to examine in depth the Role of Islamic Religious Education Teachers in Improving Student Achievement at SDN Alang-Alang Caruban I Jogoroto Jombang. This study uses a qualitative descriptive qualitative method because the researcher tries to understand and describe and seek data through interviews, observation, and documentation. This research concludes that Islamic Religious Education teachers play a role: As a teacher, namely the teacher conveys the learning objectives to be achieved As a facilitator which the teacher prepares material taken from textbooks or from other references. As a motivator, namely someone who gives encouragement or stimulation to students by developing the talents of children who excel. As an evaluator of teacher activities to evaluate students..